Effect of probiotic supplementation on plasma metabolite profile after Roux-Y gastric bypass: a prospective, randomized, double-blind, placebo-controlled clinical trial - Ramos, Marília Rizzon Zaparolli; Felicidade, Ingrid [UNESP]; de Oliveira Carlos, Lígia; Wagner, Nathalia Ramori Farinha; Mantovani, Mário Sérgio; de Lima, Luan Vitor Alves; Ribeiro, Lúcia Regina [UNESP]; Lopes, Thiago Inácio Barros; Henrique-Bana, Fernanda Carla; Zimmerman, João Vitor; Macedo Junior, Fernando Cesar; da Cruz, Magda Rosa Ramos; et al. (Springer Nature, 2022)
Background/objective: There is evidence that metabolic profile changes after Roux-Y gastric bypass (RYGB), especially due to modifications in the gastrointestinal tract. In addition, previous studies have suggested that probiotics can modify the microbiome and produce metabolites important for metabolic health maintenance. In this sense, the aim of this study was to verify the influence of probiotic supplementation on the plasma metabolite profile after RYGB. Methods: This was a randomized, double-blind, placebo-controlled clinical trial conducted with 31 patients subjected to RYGB surgery, randomized in probiotic group that was supplemented with a probiotic supplement (FloraVantage®) for 3 months after surgery or a placebo group. Plasma metabonomics was performed using nuclear magnetic resonance (NMR) at the preoperative period (T0) and at 45–50 days (T1) and 90–95 days (T2) during the postoperative period/intervention. Results: Reductions in trimethylamine-N-oxide (TMAO) and alanine were observed in both groups, however this reduction was greater in the probiotic group (TMAO 13.82%, p = 0.01 and alanine 14.03%, p = 0.03) at T2. Additionally, β-hydroxybutyrate (BHB) levels increased 10.77% in the probiotic group (p = 0.03) compared to the placebo group at T2. Conclusion: Supplementation with Lactobacillus acidophilus NCFM and Bifidobacterium lactis Bi-07 was able to associate with significant differences in relevant plasma metabolites associated with improved metabolic health.